Teacher’s challenges on ICT: Policy & literacy (Concept : Community Concern for English Pedagogy and Teaching, 2023)
In the modern digital era, ICT is used in numerous fields, including English language teaching.  ICT in education has the potential to make teaching and learning easier for both teachers and students. However, having an understanding of ICT as a teacher involves more than just implementing ICT in class, the teacher must also be aware of whether the school is implementing ICT policies. In addition, the teacher must also be literate in ICT, and one effort is to attend training. The objectives of this research are to investigate the challenges of English teachers regarding ICT policy in schools and to find out the challenges of English teachers in exploring ICT literacy. This study used a qualitative descriptive design. The respondents in this study are two English teachers from SMK Budi Tresna Muhammadiyah Cirebon. In this study, the researcher used structured interviews as an instrument. The results showed that English teachers experienced challenges related to ICT policy in school: (a). Lack of ICT facilities in schools. and English teachers experienced challenges in exploring ICT literacy: (a). Lack of ICT training in schools, (b). Lack of information about ICT training  Keyword: ICT; education; ELT; challenges; teachers